Goal-orientation and teacher motivation among teacher applicants and student teachers - Malmberg, L (2006)
The relationship between goal-orientation, intrinsic/extrinsic motivation for the teaching profession, previous achievement and entrance scores was investigated among teacher applicants (Study 1; N = 230), and student teachers (Study 2; N = 114). Utilizing path-analyses the following relationships were found in both studies, between: (a) mastery goals and intrinsic motivation, (b) avoidance goals and extrinsic motivation, (c) previous achievement and performance goals, and (d) intrinsic motivation and entrance scores. In sum the findings suggested that goal-orientation was instrumental for long-term teacher motivation and that teacher motivation, in turn, formed a basis for goal-orientation during teacher studies. © 2005 Elsevier Ltd. All rights reserved.